Prolonged Stay in the Intensive Care Unit: A Retrospective Analysis of Six Years - Onur BARAN; Ayhan ŞAHİN; Ahmet GÜLTEKİN; Cavidan ARAR (Namık Kemal Tıp Dergisi, 2023)

(untitled)
Aim:A prolonged intensive care unit stay (ICU) is associated with many factors and causes various problems. This study aims to evaluate the clinical characteristics and the factors that led to the stay of the patients treated in the ICUs for 30 days and more.Materials and Methods:The data of 178 patients were analyzed retrospectively. Those with an ICU stay of 7-29 days (n=89) were assigned as “ICU stay day <30 days - Group 1” and those with a stay of 30 days and more (n=89) were assigned as “ICU stay day ≥30 days - Group 2”. The factors related to a prolonged ICU stay were investigated in this study. The data obtained from the hospital data system were compared.Results:The age and gender distributions of the 178 patients were not statistically different between the two groups (p=0.355 and p=0.758, respectively). The group with an ICU stay of ≥30 days had a significantly higher tracheostomy rate (p<0.05) than the group with an ICU stay of <30 days. In this study, percutaneous endoscopic gastrostomy procedures were used more frequently on patients who stayed in the ICU for 30 days or more than on those who stayed for less than 30 days (p=0.000).Conclusion:Prolonged ICU stay are caused by multiple factors, and palliative care units and home care facilities must be used frequently to make the best use of ICU beds and to prevent prolonged ICU stays, which cause increased mortality and negative financial outcomes.